Fingerprint Ridge Density Of Convicted Male And Females Prisoners : A Pilot Study - Maninder Kaur (Brazilian Journal of Forensic Sciences, Medical Law and Bioethics, 2019)
The present cross-sectional study is an attempt to compare fingerprint ridge density of convicted male and female prisoners. Ridge density was determined on 125 prisoners (77 males, 48 females) by diagonally counting numbers of ridges with in a defined area in radial region of the fingertip. Contrary to previous studies convicted male prisoners of present study showed higher ridge density than their female counterparts, although differences were not statistically significant except at digit V of right hand. This trend was further confirmed by probability of proportions, and likelihood ratio of digit V of convicted prisoners exhibiting ridge density of 17 or more was most likely to be of male origin and ridge density of 14 or less was most likely to be of female origin with divergent behaviour.